A Case of Mixed Infections in a Patient Presenting with Acute Febrile Illness in the Tropics - L. S. Yong; K. C. Koh (Case Reports in Infectious Diseases)
Concurrent infections with more than one etiological agent can result in an illness with overlapping symptoms, resulting in a situation where the diagnosis and management of such a patient could be challenging. We report a case of vivax malaria in a patient who was also serologically positive for leptospirosis and dengue.